2010
DOI: 10.3340/jkns.2010.48.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Enteral Nutrition on In-Hospital Mortality in Patients with Hypertensive Intracerebral Hemorrhage

Abstract: Objective : We conducted this study to evaluate the clinical impact of early enteral nutrition (EN) on in-hospital mortality and outcome in patients with critical hypertensive intracerebral hemorrhage (ICH). Methods : We retrospectively analyzed 123 ICH patients with Glasgow Coma Scale (GCS) score of 3-12. We divided the subjects into two groups : early EN group (< 48 hours, n = 89) and delayed EN group (≥ 48 hours, n = 34). Body weight, total intake and output, serum albumin, Creactive protein, infectious com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In logistic regression analysis, after adjusting for potential confounders, we also found that GCS score was independently associated with severity on admission and in‐hospital mortality after PICH, whereby the lower GCS score on admission, the worse severity on admission and greater in‐hospital mortality. These findings correspond with results from many previous studies in which the initial consciousness level evaluated by GCS score was the most important and consistent predictor of ICH outcome and mortality .…”
Section: Discussionsupporting
confidence: 91%
“…In logistic regression analysis, after adjusting for potential confounders, we also found that GCS score was independently associated with severity on admission and in‐hospital mortality after PICH, whereby the lower GCS score on admission, the worse severity on admission and greater in‐hospital mortality. These findings correspond with results from many previous studies in which the initial consciousness level evaluated by GCS score was the most important and consistent predictor of ICH outcome and mortality .…”
Section: Discussionsupporting
confidence: 91%
“…A large RCT compared EEN (“as soon as possible”) to no nutrition within 7 days and reported a trend towards reduction of long-term mortality (6 months) with EN, with an increased risk of poor neurologic outcome in survivors [ 30 ]. An observational study reported reduction in infectious complications with EEN vs. delayed EN [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Early (enteral) feeding (ie, within 48 hours) should be considered in ICH patients as it is associated with reduced risk of pneumonia and improved survival 23. High blood glucose in the acute phase of ICH shows a continuous relation with early deterioration, poor functional outcome and higher mortality regardless of diabetic status 24.…”
Section: Control Of Bp and Other Physiological Variablesmentioning
confidence: 99%